2020
DOI: 10.1101/2020.10.25.20219105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public Transit Ridership Analysis During the Covid-19 Pandemic

Abstract: This study investigates the effect of the coronavirus (COVID-19) pandemic on public transport ridership in Baltimore and nine other U.S. cities similar to Baltimore, in terms of population and service area, during the first five months of 2020. The analysis is based on ridership numbers, vehicle revenue hours, and vehicles operated in maximum service. A compliance analysis was done between 2020 and 2019, as well as a monthly analysis of 2020 by mode and type of services. In comparison to 2019, the ridership de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 18 publications
1
35
0
1
Order By: Relevance
“…The COVID-19 pandemic brought a dramatic reduction in the use of mass transit as people both reduced their travel and shifted to other modes, afraid of getting infected on crowded buses, subways, and rail cars (Abdullah et al 2020;Ahangari et al 2020;Aloi et al 2020; Jenelius and Cebecauer 2020) (Figure 6). In some systems, ridership fell by more than 90% (Aloi et al 2020;Liu et al 2020;Olin 2020).…”
Section: Changing Modes Of Travel?mentioning
confidence: 99%
“…The COVID-19 pandemic brought a dramatic reduction in the use of mass transit as people both reduced their travel and shifted to other modes, afraid of getting infected on crowded buses, subways, and rail cars (Abdullah et al 2020;Ahangari et al 2020;Aloi et al 2020; Jenelius and Cebecauer 2020) (Figure 6). In some systems, ridership fell by more than 90% (Aloi et al 2020;Liu et al 2020;Olin 2020).…”
Section: Changing Modes Of Travel?mentioning
confidence: 99%
“…In Baltimore, passenger numbers began to decline from March 2020, while in Washington, Detroit, Seatle, Minneapolis and several others, passenger numbers were recorded as early as April 2020 (Ahangari et al, 2020). This phenomenon has also been observed in India.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Some studies explored the causes of high risk of mass transit due to density, diversity of contact, and high probability of infected person mobility due to non-tracking system which in turn leads to the public reduction to use of mass transit [23,24]. Further, researchers have studied that there is a significant reduction in ridership of public transportation due to the perceived risk of COVID-19 by the public [14,25,26]. A Sweden-based study showed a 40-60% reduction in ridership of public transportation due to the risk perception of lower active public transport users [27], whereas researchers have shown that the reasons behind the risk being infected are mass mobility with congested cases, the behaviour of co-travellers with COVID protocol, and fear of becoming infected [28].…”
Section: Impact Of Pandemic Conditions On Transportationmentioning
confidence: 99%